Comparison of Endoscopic Versus Percutaneous Approach (Blind) to Control the Obturator Jerk in Patients Undergoing Transurethral Resection of Bladder Tumors Under Spinal Anesthesia (Bangladesh Journal of Urology, 2020)
Objective: The aim of the study was to compare the endoscopic versus percutaneous approach (blind) to control the obturator jerk in patients undergoing transurethral resection of bladder tumors under spinal anesthesia.Materials and methods: A prospective observational study was performed in Department of Urology, Chittagong Medical College, Chittagong and some Private Hospitals (Ltd.) in Chittagong city during the period from January 2016 to June 2016. Total 100 patients were grouped into two, on alternate basis. Fifty(50) patients in group- A conducted with endoscopic infiltration with 20ml of injection 2% lignocaine at the bladder tumor base and another 50 patients in group-B, conducted with blind percutaneous technique with same drug and volume ( 20ml inj.2% lignocaine) to control obturator jerk. Severity of obturator jerk in both procedure, percentage of complete resection, ONB procedure related time, ONB procedure related complications and surgeon’s satisfaction level were recorded and compared between two approaches. Chi-square analysis was performed to compare the ease of approach and outcome of the two techniques. A value of P